Textbook Analysis of Al-ʿArabiyyah Baina Yadai Aulādinā Vol 1 in The Rusydi Ahmad Thuaimah’s Perspective - Sapitri, Nurlaila; Nasution, Sahkholid; Iskandar, Topan (Asalibuna, 2023)
Compiling a book that will be used as a teaching material requires precision. Compiling a textbook that is not based on good textbook standards will affect the results and learning process. The purpose of this study is to determine the suitability of the compilation of an Arabic textbook according to the criteria of Rusydi Ahmad Thuaimah's analysis of Arabic textbooks in terms of 1) book publishing, 2) language and teaching, 3) culture and teaching, 4) practice and evaluation, 5) accompanying book. This study uses a qualitative approach with content analysis method. The results of the study show that the level of suitability with the perspective of Rusydi Ahmad Thuaimah in terms of the compilation of Arabic textbooks is as follows: 1) from the perspective of book publishing and design 72%, 2) from the aspect of language and teaching 73%, 3) from the aspect of culture and teaching 60%. While 4) from the aspect of training and evaluation 83%, and 5) In terms of accompanying the book, 95%. Thus, the book has a proficient level of suitability with the criteria according to Thuaimah's perspective. Further research needs to focus on teacher experience in teaching the book.